Generalized dualities and supergroups - Daniel Butter; Falk Hassler; Christopher N. Pope; Haoyu Zhang (Journal of High Energy Physics, 2023)
Abstract Using a recently developed formulation of double field theory in superspace, the graviton, B-field, gravitini, dilatini, and Ramond-Ramond bispinor are encoded in a single generalized supervielbein. Duality transformations are encoded as orthosymplectic transformations, extending the bosonic O(D, D) duality group, and these act on all constituents of the supervielbein in an easily computable way. We first review conventional non-abelian T-duality in the Green-Schwarz superstring and describe the dual geometries in the language of double superspace. Since dualities are related to super-Killing vectors, this includes as special cases both abelian and non-abelian fermionic T-duality. We then extend this approach to include Poisson-Lie T-duality and its generalizations, including the generalized coset construction recently discussed in [ arXiv:1912.11036 ]. As an application, we construct the supergeometries associated with the integrable λ and η deformations of the AdS5 × S5 superstring. The deformation parameters λ and η are identified with the possible one-parameter embeddings of the supergravity frame within the doubled supergeometry. In this framework, the Ramond-Ramond bispinors are directly computable purely from the algebraic data of the supergroup.